Levels of metabolizable energy and digestible lysine for broiler chicks 8-21 days of age - Nunes R.V. (2015)
The experiment was conducted with the objective of evaluating the effect of metabolizable energy (ME) levels and digestible lysine (DL) levels on the performance of 8-21 days old broiler chicks. Eight hundred and sixty four broiler chicks were used, with average weight of 160 ± 5g, randomly distributed in 48 boxes (experimental unit), experimental unit in a factorial 4×4 with four levels of ME (2,700, 2,825, 2,950, and 3,075 kcal kg-1) and four levels of DL (1,080; 1,187; 1,295 and 1,403%) resulting in 16 treatments with three replications. Increases in levels of ME and DL in the diets caused significant interaction (P <0.05) in weight gain and feed conversion. Increasing levels of ME and DL caused significant interaction (P <0.05) for the deposition rate of protein and fat in the carcass. The simultaneous increases of ME and DL in the diet promoted a linear increase (P <0.05) in villus height of the duodenum, jejunum, and villous:crypt ileum. It is recommended the use of 3,075 kcal kg-1 ME and 1,403% of LD for best performance, protein deposition rate, and intestinal morphometric characteristics of 8-21 days old broiler chicks.